Resposta imune ao componente pertussis da vacina dTpa em gestantes do município de Cuiabá - Molina, Mariela da Gama Fortunato (2017)
Faced with the reemergence of pertussis in Brazil and the world over the last two decades, even in countries with high vaccination coverage, it was necessary to create strategies to control pertussis to reduce the morbidity and mortality of pertussis infants until they receive primary DTP immunization. In Brazil, this is the first study that evaluates the immune response of the pertussis component of the tetanus, diphtheria, and acellular pertussis (dTpa) in pregnant women after the implantation of this strategy. Objective: To evaluate the immune response to the pertussis component of the dTpa vaccine in pregnant women in the city of Cuiabá. Method: A cross-sectional study with healthy pregnant women who performed prenatal care in two university hospitals. The pre-dTpa sample was collected during prenatal and post-dTpa samples, at delivery. Antibody assays were performed using the enzyme-linked immunosorbent assay. Results: The final sample consisted of 48 pregnant women, with a mean age of 28 years; 56.25% black and 43.75% white; 87.50% had a partner; 33.33% were housewives; About 1/3 had incomplete high school and 1/3 upper level. The majority had complete prenatal care (83.33%), had a cesarean delivery (66.67%), were multiparous (79.17%) and received the dTpa vaccine with a mean gestational age of 32.94 weeks. Differences between post-dTpa and pre-dTpa IgG dosages showed significant increases for all antigens tested (p <0.0001). In post-dTpa, the mean increases of the antibodies (IU/mL) and their respective standard deviations were: filamentous hemagglutinin = 701.20 + 942.90; pertussis toxin = 97.34 + 84.07 and pertactin = 1,159.00 + 1714.00. According to criteria defined by Huygen et al. (2015), did not respond to the pertussis antigens of dTpa: 7/48 vaccine (14.58%) for filamentous hemagglutinin; 11/48 (22.92%) for pertussis toxin; 8/48 (16.66%) for pertactin. Conclusions: There were significant increases in post-vaccine antibody concentrations for all pertussis antigens present in the dTpa vaccine, indicating a good immune response for pertussis in pregnant women at the time of birth of their newborns. No relation was found between the increase in the vaccine response to the pertussis antigens present in the dTpa vaccine with: maternal age, 6 or more prenatal consultations, social stratum, gestational age at the time of the vaccine before or after 33 weeks and interval (days) between the dTpa vaccine and childbirth.